Design of sustainable geopolymeric matrices for encapsulation of treated radioactive solid organic waste - Santi, Andrea; Mossini, Eros; Magugliani, Gabriele; Galluccio, Francesco; Macerata, Elena; Lotti, Paolo; Gatta, Giacomo Diego; Vadivel, Dhanalakshmi; Dondi, Daniele; Cori, Davide; Nonnet, Hélène; Mariani, Mario (Frontiers in Materials, 2022)
Among radioactive by-products generated by nuclear technologies, solid organic waste is drawing attention because of difficult management and incompatibility with the disposal strategies traditionally adopted. Recently, geopolymers have been proposed as valid and green alternatives to cement-based matrices. In this work, novel geopolymeric formulations have been studied at laboratory scale to encapsulate ashes from incineration of surrogate solid organic waste and to further pursue sustainability and circular economy goals. Indeed, the most widely used precursor of literature geopolymers, calcined kaolin, has been totally replaced by natural raw materials and recycled industrial by-products. In addition, a highly zeolitized volcanic tuff has been chosen to further improve the intrinsic cation-exchange capacity of the geopolymer, hence enhancing waste-matrix interaction. The alkaline activation of the precursors, achieved without silicates of any metal, resulted in a promisingly durable geopolymeric matrix, whose chemical composition has been optimised to provide compressive strength above 10 MPa after 28 days of curing. A water-saturated sealed chamber provided the optimal curing condition to limit the efflorescence and improve the mechanical properties. At least 20 wt% loading of treated surrogate waste was achieved, without compromising workability, setting time, and compressive strength, the latter remaining within acceptable values. In order to demonstrate matrix durability, leaching behaviour and thermal stability were preliminarily assessed by immersion tests and thermogravimetric analyses, respectively. The leachability indices of constituent elements resulted far above 6, which is the generally agreed requirement for cement-based matrices. Moreover, the mechanical resistance was not worsened by the water immersion. The preliminarily obtained results confirm the promising properties of the new matrix for the immobilization of nuclear waste.